Manajemen Strategi Badan Penanggulangan Bencana Daerah Dalam Penanggulangan Banjir Di Kabupaten Bekasi - Shufi Soenarto Putri; Hanny Purnamsari; Ani Nurdiani Azizah (JIAP (Jurnal Ilmu Administrasi Publik), 2021)
Floods are a social problem that often occurs almost every year. Bekasi Regency in recent years has become a regular flood with the number of submerged areas increasing every year and causing losses in various aspects of life. This is quite a concern and raises questions from the public about how the government's role in flood prevention is, so it is necessary to know the strategic management carried out by the BPBD which is the hand of the Bekasi Regency Government in dealing with floods and their prevention and mitigation. This study uses a descriptive method with a qualitative approach, data collection techniques are carried out through interviews, observations, and documentation using strategic management theory according to Wheelen and Hunger (2008) which have four stages: environmental analysis, strategy formulation, strategy implementation, evaluation and control. The results of this study indicate that the strategic management carried out by BPBD in flood prevention in Bekasi Regency has not been optimal. This is because there are still shortcomings and weaknesses both from BPBD itself and from the community, lack of resources and the absence of strong legality regarding disaster risk studies and education that lacks bad habits of people who still throw garbage in rivers so that it can affect the implementation of the program that is used as a strategy by BPBD.